Pinkalicious and the merminnies - Kann, Victoria (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2020)
When Splash the merminnie's flashy tricks get him in trouble, it's up to Pinkalicious and her friends to save him.
Ages 4-8.
DMM01/20.
Keywords: Pinkalicious (Fictitious character) -- Juvenile fiction; Mermaids -- Juvenile fiction